Dermapedia. An atlas of topographic Pediatric Dermatology. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
When facing a child with skin lesions pediatricians and dermatologists can sometimes have doubts and feel the need to compare what they see with already confirmed diagnostic images. To this need responds DERMAPEDIA, an encyclopedia of images and texts, ranked according to topographical criteria. For the non-specialist doctor but also for the skilled physician the distribution of the lesions is in fact more important than the fine morphology...